(untitled) (Research, Society and Development, 2020)
Objective: to assess the satisfaction and expectations of pregnant women with prenatal care realized in basic health service in a Brazilian Midwest city. Methods: quantitative cross-sectional study whose sample consisted of 107 pregnant women attended in basic health service, aged 18 years or over and attended at least three prenatal appointments. It was used an instrument with sociodemographic variables and the Brazilian version of Patient Expectations and Satisfaction whit Prenatal Care (PESPC). Statiscal analysis was performed using the independent t test, with statistical significance at 5%. Results: average age of 25.6 (SD=5, 7) years; most married (80, 4%); brown-skinned (62, 6%); housewife (46, 7%); monthly family income up to two minimum wages (43,9%); four to seven years of study (58, 9%); gestational age ranged from 15 to 39 weeks of gestation, more than one pregnancy (38, 3%); one parturition (37, 4%) and one child (37,4%). Satisfaction was associated with complications in the previous pregnancy (p<0, 05). Conclusion: the satisfaction of the pregnant women demonstrated a positive level in terms of professional care, the form of treatment received the interest of the team in transmitting information, the ease of scheduling appointments and carrying out tests during the prenatal care period.